The Complete Short Stories. A Good Hanging. Beggars Banquet. Atonement - Rankin I. Ian (London, Orion, 2005)
Over the course of his career, Ian Rankin has amassed an incredible portfolio of short stories. Published in crime magazines, composed for events, broadcast on radio, they all share the best qualities of his phenomenally popular novels. Now Ian Rankin's two critically acclaimed short story collections — A Good Hanging and Beggars Banquet — come together in one volume, along with Atonement, a new Rebus story written especially for this collection. A GOOD HANGING Twelve Inspector Rebus mysteries, including the hanging of a student during the Edinburgh Festival, a gruesome arson attack and the apparent witnessing of a miracle. Step off the tourist trail and into the macabre heart of Rebus's Edinburgh . .. BEGGARS BANQUET Ranging from the suburban murders of loved ones to the sinister workings of a serial killer's mind and from a bent cop with a terminal approach to his work, to a hitman who gets more than he bargained for in a crowded fairground, here are twenty-one tales that all bear the hallmark of great crime writing. The collection includes seven Inspector Rebus mysteries and the Dagger award-winning story Herbert in Motion. Born in the Kingdom of Fife in 1960, Ian Rankin graduated from the University of Edinburgh and spent three years writing novels when he was supposed to be working towards a PhD in Scottish Literature. His books have been translated into twenty-two languages and regularly appear on bestseller lists worldwide. He is the winner of four Crime Writers' Association Dagger awards, including the prestigious Diamond Dagger, and America's celebrated Edgar award. In 2002, Ian received the OBE, opting to receive the prize in his home city of Edinburgh, where he lives with his partner and two sons.